Male-specific insecticide resistance and mosquito transgene dispersal. - Sinkins, S; Hastings, I (2004)
There is a need to develop methods to spread disease-blocking transgenes through mosquito populations. This article discusses the possibility of linking transgenes to insecticide-resistant alleles engineered to be expressed only in males. The resulting increase in mean longevity of males carrying the construct under insecticide treatment could easily outweigh any fitness costs in females, so that the construct would spread rapidly. It should be possible to produce constructs where any potential risk of loss of male-specific expression would be negligible.